Wide-distribution zirconia-aminated carbon quantum dot nanofluid as well as preparation and application thereof
Through the design of wide-distribution zirconia-aminated carbon quantum dot nanofluids, the problems of poor oil-driving effect and environmental pollution in the existing technology are solved, and efficient nano-oil repellent effect and environmentally friendly oil recovery are achieved. process.
Patent Information
- Application Number
- CN202310753923.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-06-25
AI Technical Summary
The existing nano-oil-driving technology has poor oil displacement effect in low-permeability/ultra-low-permeability reservoirs, complex process and environmental pollution. The nanoparticle size is larger than that of quantum dots, resulting in small impact volume, which cannot effectively improve recovery rate.
Using wide-distribution zirconia-aminated carbon quantum dot nanofluids, the stable aminated carbon quantum dots are connected through amide bonds to form a composite of nanozirconia and combined with deionized water to achieve self-stability and high wave volume of nanofluids .
The mining efficiency of low permeability/ultra-low permeability reservoirs is improved, the injection pressure is reduced, and the oil displacement efficiency is enhanced. There is no need for additional surfactant, which significantly improves the recovery rate.
Smart Images

Figure CN119193130A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nano oil displacement, and in particular to a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid and preparation and application thereof. Background Art
[0002] Hydrocarbon fuels will continue to be the main energy source for human society for some time to come. The innovation of oil exploration and enhanced oil recovery (EOR) technology is the focus of the oil and gas industry, with the goal of improving the oil recovery rate of currently exploited reservoirs and unconventional oil and gas resources. Nanoparticles have great potential in the field of EOR in low / ultra-low permeability reservoirs. Their advantages are: (1) they can be flexibly customized by combination, chemical modification, etc.; (2) their unique mechanical and thermal stability can withstand the harsh environmental conditions of underground reservoirs such as high temperature, high pressure, strong shear, and high salinity; (3) their interfacial activity can change the wettability of the rock surface, exfoliate the crude oil in the pore throat in the form of small oil droplets, and then displace it. Therefore, nanofluids prepared with water as the carrier and nanoparticles as the dispersed phase are ideal media for displacing low / ultra-low permeability reservoirs.
[0003] As a typical representative of zero-dimensional nanomaterials, carbon quantum dots are in the nanoscale range (1nm to 10nm) in three-dimensional space, have unique physical and chemical properties, and are an emerging EOR technology to solve the problem of nanoscale pore throat displacement. "Continuous hydrothermal flow synthesis of S-functionalised carbon quantum dots for enhanced oil recovery" in Volume 405 of Chemical Engineering Journal in 2021 reported that the use of nanofluids containing 0.01wt% carbon quantum dots to displace limestone tight reservoirs increased the oil recovery by 17±0.2%. Under high temperature and high salt conditions, carbon quantum dots exhibit strong colloidal stability. Through the study of the oil displacement mechanism of carbon quantum dots, it was found that in addition to changing the wettability of rocks, its small size effect will temporarily block the nanopore throats. As the displacement agent is continuously injected, the pressure of the pores around the pore throats will increase, thereby improving the removal efficiency of the attached oil. As more retained oil is removed, the pressure decreases, and the particle aggregates dissociate and redisperse into the nanofluid.
[0004] CN104531118A discloses an intelligent nano oil-displacing agent, wherein the main component of the nanofluid is selected from one or more of silicon dioxide nanoparticles, silicon nanoparticles, calcium carbonate nanoparticles, calcium oxide nanoparticles, graphite powder, copper oxide nanoparticles, and zinc oxide nanoparticles, and after surface modification with functional monomers, the intelligent nano oil-displacing agent is prepared by mixing with a surfactant and an alkali. The nanoparticles used are conventional materials and do not reach the quantum dot size level. All nanoparticles are surface modified by a one-pot method, and the similarities and differences in the interaction between the properties of different nanomaterials themselves and the rock reservoir and oil droplets are eliminated, and an additional surfactant needs to be added, which increases the complexity of the system.
[0005] The main component of the nanofluid disclosed in CN110964491A is polymer nanoparticles with a particle size of 10nm to 1000nm, which are directly prepared in a medium by a reverse microemulsion polymerization method. The monomers and organic solvents in the preparation process of the nanofluid are toxic and cause environmental pollution. The polymer nanofluid injected underground will also cause environmental pollution. The particle size of the nanoparticles is larger than that of quantum dots, and the swept volume is relatively low.
[0006] CN114956052A provides a method for preparing carbon quantum dots, using aldehyde and alkali as core raw materials, forming carbon quantum dots of 1nm to 10nm through cross-linking polymerization, using a capping agent to control the particle size of the carbon quantum dots, and using an activator to enhance the interfacial activity of the carbon quantum dots. The nanofluid is a solution made of a single carbon quantum dot, there is no stabilizer in the system, the quantum dots are easy to agglomerate, and the particle size distribution is narrow. Summary of the invention
[0007] The purpose of the present invention is to provide a wide distribution zirconium oxide-aminated carbon quantum dot nanofluid and its preparation and application. The present invention designs and prepares a new type of nanofluid to achieve a better oil recovery effect. The present invention solves the problem of inefficient oil recovery of water flooding technology in low permeability / ultra-low permeability reservoirs, as well as the problems of cumbersome process, complex system, environmental pollution, small core micropore wave and volume of general nano oil recovery technology, and improves the efficiency of crude oil recovery.
[0008] In order to achieve the above purpose, the present invention adopts the following technical solutions:
[0009] The first aspect of the present invention provides a broad distribution zirconium oxide-aminated carbon quantum dot nanofluid, the nanofluid comprising nano zirconium oxide, aminated carbon quantum dots and water;
[0010] The solid content of the nanofluid is 0.001% to 0.2%; wherein the mass ratio of the nano zirconium oxide to the aminated carbon quantum dots is (3 to 5):3;
[0011] The aminated carbon quantum dots include carbon quantum dots and polyethyleneimine connected to the carbon quantum dots via amide bonds.
[0012] According to the nanofluid of the present invention, preferably, the aminated carbon quantum dots are obtained by amidation reaction between carboxyl carbon quantum dots and polyethyleneimine.
[0013] The carboxyl carbon quantum dots have carboxyl groups, and the polyethyleneimine (PEI) has amino groups, and the two are connected by an amide bond generated by an amidation reaction; in the resulting aminated carbon quantum dots, the quantum dots and polyethyleneimine (PEI) are connected by an amide bond (covalent bond). The stability of covalent bonds is higher than that of ionic bonds and hydrogen bonds, and can be used for oil recovery in high-temperature chemical environments of reservoirs.
[0014] According to the nanofluid of the present invention, preferably, the water is deionized water.
[0015] According to the nanofluid of the present invention, preferably, the particle size of the nano zirconium oxide is in the range of 20 nm to 900 nm, more preferably 50 nm to 300 nm.
[0016] According to the nanofluid of the present invention, preferably, the particle size range of the aminated carbon quantum dots is 2 nm to 10 nm, more preferably 5 nm to 10 nm.
[0017] According to the nanofluid of the present invention, preferably, the particle size of the nano zirconium oxide is in the range of 50 nm to 300 nm, and the particle size of the aminated carbon quantum dots is in the range of 5 nm to 10 nm.
[0018] According to the nanofluid of the present invention, preferably, the solid content of the nanofluid is 0.01% to 0.2%.
[0019] The nano-zirconia with different particle sizes used in the present invention can be obtained through commercial purchase, and the carboxyl carbon quantum dots can also be obtained through commercial purchase, for example, from Xi'an Qiyue Biotechnology Co., Ltd.
[0020] According to the nanofluid of the present invention, preferably, the specific preparation process of the aminated carbon quantum dots includes:
[0021] Dispersing carboxyl carbon quantum dots in a reaction medium, adding a condensing agent and an activator solution and stirring evenly; then adding a polyethyleneimine solution to react to obtain a solution containing the aminated carbon quantum dots;
[0022] The obtained solution is centrifuged, washed with water until neutral, and dried to obtain the aminated carbon quantum dots.
[0023] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the reaction medium is selected from at least one of deionized water, N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, tetrahydrofuran, tert-butyl methyl ether, cyclopentyl methyl ether, dimethyl carbonate, ethyl acetate, isopropanol, 2-methyltetrahydrofuran, 2-(N-morpholine)ethanesulfonic acid, acetonitrile, methanol, and ethanol.
[0024] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the reaction medium is deionized water.
[0025] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the condensing agent is selected from one of a carbodiimide condensing agent, an organophosphorus condensing agent, an onium salt condensing agent, and other condensing agents (3-acyl-2-thiothiazoline, tris(2,6-dimethoxyphenyl)bismuth, N,N'-carbonyldiimidazole, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride).
[0026] The carbodiimide condensing agent includes 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, O-(5-norbornene-2,3-dicarbonimide)-N,N,N',N'-tetramethyluronium tetrafluoroboric acid, etc.; the organophosphorus condensing agent includes 2-(7-azobenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate, O-(benzotriazole-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, 6-chlorobenzotriazole-1,1,3,3-tetramethyluronium hexafluorophosphate, diphenylphosphoryl chloride, diethyl cyanophosphate, diphenylphosphoryl azide, thiodimethylphosphoryl azide, di(2-oxy-3- The onium salt condensing agent includes O-(7-azabenzotriazol-1-yl)-bis(tetrahydropyrrolyl)carbonium hexafluorophosphate, O-(benzotriazol-1-yl)-bis(tetrahydropyrrolyl)carbonium hexafluorophosphate, O-(benzotriazol-1-yl)-bis(dimethylamino)carbonium hexafluorophosphate, )carbonium tetrafluoroborate, O-(N-succinimidyl)-bis(dimethylamino)carbonium tetrafluoroborate, benzotriazol-1-yloxy-tris(dimethylamino)phosphonium hexafluorophosphate, benzotriazol-1-yloxy-tris(tetrahydropyrrolyl)phosphonium hexafluorophosphate, (3H-1,2,3-triazolo[4,5-b]pyridine-3-oxy)tri-1-pyrrolidinyl hexafluorophosphate, etc.
[0027] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the condensation agent is dimethylaminopropylethylcarbodiimide hydrochloride.
[0028] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the active agent is selected from one of N-hydroxysuccinimide, 4-dimethylaminopyridine, 4-pyrrolidinopyridine, 1-hydroxybenzotriazole, 1-hydroxy-7-azobenzotriazole, N-hydroxysuccinimide, N-hydroxyphthalimide, pentafluorophenol, triethylamine, diazabicyclic, and pyridine.
[0029] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the active agent is N-hydroxysuccinimide.
[0030] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the solvent of the polyethyleneimine solution is the same as the reaction medium, preferably deionized water; the concentration of the polyethyleneimine solution is 2% to 50%, more preferably 5% to 20%.
[0031] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the polyethyleneimine is selected from at least one of linear polyethyleneimine and branched polyethyleneimine, and the molecular weight of the polyethyleneimine is 1500 to 20000, more preferably 8000 to 18000.
[0032] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the molar ratio of the carboxyl carbon quantum dots, the condensation agent, the activator and the polyethyleneimine is 1:(1-2):(1-2):1.
[0033] More preferably, the molar ratio of the carboxyl carbon quantum dots, the condensation agent, the activator and the polyethyleneimine is 1:1.5:1.5:1.
[0034] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the reaction temperature is -30°C to 40°C; more preferably, 0°C to 25°C.
[0035] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the reaction time is 2 h to 24 h; more preferably, 12 h to 24 h.
[0036] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the centrifugal rotation speed is 20000 rpm to 150000 rpm; more preferably, 25000 rpm to 30000 rpm.
[0037] In the preparation process of the aminated carbon quantum dots of the present invention, preferably, the drying temperature is room temperature.
[0038] The second aspect of the present invention provides at least one method for preparing zirconium oxide-aminated carbon quantum dot nanofluid, which comprises: dispersing nano zirconium oxide and aminated carbon quantum dots in water to obtain the zirconium oxide-aminated carbon quantum dot nanofluid.
[0039] The third aspect of the present invention provides one or more zirconium oxide-aminated carbon quantum dot nanofluids for use in water flooding of low permeability / ultra-low permeability reservoirs.
[0040] The beneficial effects of the present invention include:
[0041] 1) The present invention selects zirconium oxide and carbon quantum dot composite nanoparticles as the main components of nanofluids for the first time, and comprehensively utilizes the high rock surface wetting reversal characteristics of nano zirconium oxide and the small size characteristics of carbon quantum dots to expand the swept volume while enhancing the oil recovery efficiency.
[0042] 2) The particle size distribution of zirconium oxide-amino carbon quantum dot composite nanoparticles is wide, and they can enter into various tiny pore throats in the rock formation, comprehensively increasing the swept volume of tiny voids, thereby improving the extraction efficiency of low permeability / ultra-low permeability oil fields.
[0043] 3) PEI is used to modify carbon quantum dots and amino groups are introduced on the surface of carbon quantum dots. The reaction process is mild and the aminated carbon quantum dots are positively charged in nanofluids. They can be used as cationic surfactants to stabilize nanofluids without the need to add additional surfactants. At the same time, they form ion pairs with the carboxylic acid groups of crude oil to better achieve the targeted oil search function.
[0044] In view of the poor water flooding effect of low-permeability / ultra-low-permeability reservoirs and the problems in the development and use of general nano-oil flooding technology, the present invention disperses nano-zirconia and aminated carbon quantum dots in deionized water after mixing, and obtains nanofluids with wide distribution, self-stability, and high sweep volume characteristics without the need to add additional surfactants. The wide-distribution zirconium oxide-aminated carbon quantum dot nanofluid prepared by the present invention has been verified by core flooding experiments, and can effectively reduce the injection pressure, play a role in reducing pressure and increasing injection, and can greatly improve the recovery rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 Schematic diagram of the zirconium oxide-aminated carbon quantum dot nanofluid of the present invention.
[0046] Figure 2 This is the infrared spectrum of the aminated carbon quantum dots prepared in Example 1 of the present invention. The infrared spectra of other examples are the same.
[0047] Figure 3 This is a transmission electron microscope photograph of the aminated carbon quantum dots prepared in Example 1 of the present invention.
[0048] Figure 4 This is the particle size distribution diagram of nano zirconium oxide in Example 1 of the present invention. DETAILED DESCRIPTION
[0049] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.
[0050] like Figure 1 As shown, the zirconium oxide-aminated carbon quantum dot nanofluid provided by the present invention comprises nano zirconium oxide, aminated carbon quantum dots and water, wherein the aminated carbon quantum dots comprise carbon quantum dots and polyethyleneimine connected to the carbon quantum dots via amide bonds. The particle size of the nano zirconium oxide is in the range of 20nm to 900nm, and the particle size of the aminated carbon quantum dots is in the range of 2nm to 10nm. The particle size distribution of the zirconium oxide-aminated carbon quantum dot composite nanoparticles is wide, and they can enter into various tiny pore throats in the rock formation, comprehensively improving the swept volume of tiny voids, thereby improving the mining efficiency of low permeability / ultra-low permeability oil fields.
[0051] PEI is used to modify carbon quantum dots and introduce amino groups on the surface of carbon quantum dots. The reaction process is mild and the aminated carbon quantum dots are positively charged in nanofluids. They can be used as cationic surfactants to stabilize nanofluids without the need to add additional surfactants. At the same time, they form ion pairs with the carboxylic acid groups of crude oil to better achieve targeted oil search functions.
[0052] Specifically, the solid content of the nanofluid is 0.001% to 0.2%, preferably 0.01% to 0.2%; wherein the mass ratio of the nano zirconium oxide to the aminated carbon quantum dots is (3 to 5):3.
[0053] In some specific embodiments of the present invention, the particle size of the nano-zirconium oxide is in the range of 50 nm to 300 nm, and the particle size of the aminated carbon quantum dots is in the range of 5 nm to 10 nm.
[0054] In some specific embodiments of the present invention, the aminated carbon quantum dots are obtained by amidation reaction between carboxyl carbon quantum dots and polyethyleneimine. The carboxyl carbon quantum dots have carboxyl groups, and the polyethyleneimine (PEI) has amino groups, and the two are connected by an amide bond generated by an amidation reaction; then in the obtained aminated carbon quantum dots, the quantum dots and polyethyleneimine (PEI) are connected by an amide bond (covalent bond). The stability of covalent bonds is higher than that of ionic bonds and hydrogen bonds, and can be used for oil displacement in high-temperature chemical environments of reservoirs. Preferably, the water is deionized water.
[0055] The nano-zirconia with different particle sizes used in the present invention can be obtained through commercial purchase, and the carboxyl carbon quantum dots can also be obtained through commercial purchase, for example, from Xi'an Qiyue Biotechnology Co., Ltd.
[0056] In some specific embodiments of the present invention, the specific preparation process of the aminated carbon quantum dots includes:
[0057] Dispersing carboxyl carbon quantum dots in a reaction medium, adding a condensing agent and an activator solution and stirring evenly; then adding a polyethyleneimine solution to react to obtain a solution containing the aminated carbon quantum dots;
[0058] The obtained solution is centrifuged, washed with water until neutral, and dried at room temperature to obtain the aminated carbon quantum dots.
[0059] In some specific embodiments of the present invention, the reaction medium is selected from at least one of deionized water, N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, tetrahydrofuran, tert-butyl methyl ether, cyclopentyl methyl ether, dimethyl carbonate, ethyl acetate, isopropanol, 2-methyltetrahydrofuran, 2-(N-morpholino)ethanesulfonic acid, acetonitrile, methanol, and ethanol; preferably deionized water.
[0060] In some specific embodiments of the present invention, the condensing agent is selected from a carbodiimide condensing agent, an organic phosphorus condensing agent, an onium salt condensing agent and other condensing agents.
[0061] The carbodiimide condensing agents include 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, dicyclohexylcarbodiimide, diisopropylcarbodiimide, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide, O-(5-norbornene-2,3-dicarbonimide)-N,N,N',N'-tetramethyluronium tetrafluoroborate, etc.; the organophosphorus condensing agents include 2-(7- azobenzotriazole)-N,N,N',N'-tetramethyluronium hexafluorophosphate, O-(benzotriazole-1-yl)-N,N,N',N'-tetramethyluronium hexafluorophosphate, 6-chlorobenzotriazole-1,1,3,3-tetramethyluronium hexafluorophosphate, diphenylphosphoryl chloride, diethyl cyanophosphate, diphenylphosphoryl azide (DPPA), dimethylthiophosphoryl azide, di(2-oxygen -3-oxazolidinyl) phosphoryl chloride, triphenylphosphine-polyhalomethane, triphenylphosphine-hexachloroacetone, triphenylphosphine-NBS, etc.; the onium salt condensing agent includes O-(7-azabenzotriazol-1-yl)-bis(tetrahydropyrrolyl)carbonium hexafluorophosphate, O-(benzotriazol-1-yl)-bis(tetrahydropyrrolyl)carbonium hexafluorophosphate, O-(benzotriazol-1-yl)-bis(dimethyl The condensing agent includes 3-acyl-2-thiothiazoline, tris(2,6-dimethoxyphenyl)bismuth, N,N'-carbonyldiimidazole, 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride, etc. Preferably, the condensing agent is dimethylaminopropylethylcarbodiimide hydrochloride.
[0062] In some specific embodiments of the present invention, the active agent is selected from one of N-hydroxysuccinimide, 4-dimethylaminopyridine, 4-pyrrolidinylpyridine, 1-hydroxybenzotriazole, 1-hydroxy-7-azobenzotriazole, N-hydroxysuccinimide, N-hydroxyphthalimide, pentafluorophenol, triethylamine, diazabicyclic, and pyridine; preferably N-hydroxysuccinimide.
[0063] In some specific embodiments of the present invention, the solvent of the polyethyleneimine solution is the same as the reaction medium, preferably deionized water; the concentration of the polyethyleneimine solution is 2% to 50%, more preferably 5% to 20%.
[0064] In some specific embodiments of the present invention, the polyethyleneimine is selected from at least one of linear polyethyleneimine and branched polyethyleneimine, and the molecular weight of the polyethyleneimine is 1500-20000, more preferably 8000-18000.
[0065] In some specific embodiments of the present invention, the molar ratio of the carboxyl carbon quantum dots, the condensation agent, the activator and the polyethyleneimine is 1:(1-2):(1-2):1; preferably 1:1.5:1.5:1.
[0066] In some specific embodiments of the present invention, the reaction temperature is -30°C to 40°C; preferably 0°C to 25°C.
[0067] In some specific embodiments of the present invention, the reaction time is 2 h to 24 h, preferably 12 h to 24 h.
[0068] In some specific embodiments of the present invention, the centrifugal rotation speed is 20000 rpm to 150000 rpm, preferably 25000 rpm to 30000 rpm.
[0069] In some specific embodiments of the present invention, the drying temperature is room temperature.
[0070] The preparation method of the above zirconium oxide-aminated carbon quantum dot nanofluid comprises: dispersing nano zirconium oxide and aminated carbon quantum dots in water to obtain the zirconium oxide-aminated carbon quantum dot nanofluid. The nanofluid can be used in water flooding of low permeability / ultra-low permeability oil reservoirs. Core flooding experiments have verified that the wide distribution zirconium oxide-aminated carbon quantum dot nanofluid prepared by the present invention can effectively reduce the injection pressure, play a role in reducing pressure and increasing injection, and can greatly improve the recovery rate.
[0071] The following provides specific examples for illustration:
[0072] All numerical designations in the examples (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values that can be appropriately changed by (+) or (-) increments of 0.1 or 1.0. All numerical designations can be understood as being preceded by the term "about".
[0073] The concentration of the PEI solution used in the following examples is 10%. The polyethyleneimine is linear polyethyleneimine, and the molecular weight of the polyethyleneimine is 1500, 8000, 12000, or 18000.
[0074] Example 1
[0075] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0076] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in deionized water, add 0.3 mol of dimethylaminopropylethylcarbodiimide hydrochloride and 0.3 mol of N-hydroxysuccinimide solution, and stir evenly.
[0077] S2. Add 0.2 mol of PEI aqueous solution with a molecular weight of 8000 to the solution obtained in step S1, and stir at 25° C. for 24 hours to obtain a solution containing the aminated carbon quantum dots.
[0078] S3. The solution obtained in step S2 is centrifuged at a speed of 25000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 5 nm.
[0079] like Figure 2 As shown in the infrared spectrum of the aminated carbon quantum dots prepared by the present invention, 3415 cm -1 The absorption peak at 1619cm is caused by the NH stretching vibration absorption peak in the amide group; -1 The absorption peaks at are the stretching vibration peaks of the carbonyl C=O in the amide group. These two strong absorption peaks confirm the existence of amide groups on the surface of carbon quantum dots.
[0080] Figure 3 This is a transmission electron microscope photo of aminated carbon quantum dots. Figure 3 It can be seen that the aminated carbon quantum dots are in uniform granular form, have good dispersion, no adhesion, and have a particle size of 2nm to 8nm, with an average particle size of 5nm.
[0081] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 300 nm and 0.05 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0082] Figure 4 is the particle size distribution of the nano zirconium oxide used, Figure 4 It can be seen that the particle size distribution of nano zirconium oxide is narrow, which is consistent with Figure 3 By compounding the aminated carbon quantum dots shown, wide-distribution composite particles with a particle size of 2nm to 300nm can be obtained.
[0083] Example 2
[0084] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0085] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in dichloromethane, add 0.3 mol of N,N'-carbonyldiimidazole HCl solution and 0.3 mol of diazabicyclo and stir evenly.
[0086] S2, adding 0.2 mol of PEI dichloromethane solution with a molecular weight of 12000 to the solution obtained in step S1, stirring at 25° C. for 24 hours to obtain a solution containing the aminated carbon quantum dots;
[0087] S3. The solution obtained in step S2 is centrifuged at a speed of 30,000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 6 nm.
[0088] S4, dispersing 0.03 g of nano zirconium oxide with a particle size of 500 nm, 0.02 g of nano zirconium oxide with a particle size of 300 nm, and 0.05 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0089] Example 3
[0090] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0091] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in dichloromethane, add 0.25 mol of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide solution and 0.25 mol of 1-hydroxybenzotriazole solution, and stir evenly.
[0092] S2. Add 0.2 mol of PEI dichloromethane solution with a molecular weight of 18,000 to the solution obtained in step S1, and stir at 25° C. for 10 hours to obtain a solution containing the aminated carbon quantum dots.
[0093] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 8 nm.
[0094] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 600 nm and 0.05 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0095] Example 4
[0096] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0097] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in ethyl acetate, add 0.25 mol of diphenylphosphoryl chloride and 0.25 mol of triethylamine and stir evenly.
[0098] S2. Add 0.2 mol of PEI dichloromethane solution with a molecular weight of 18,000 to the solution obtained in step S1, and stir at 0° C. for 10 hours to obtain a solution containing the aminated carbon quantum dots.
[0099] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 10 nm.
[0100] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 900 nm and 0.05 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0101] Example 5
[0102] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0103] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in ethanol, add 0.25 mol of triphenylphosphine-tetrabromomethane and 0.25 mol of triethylamine and stir evenly.
[0104] S2. Add 0.2 mol of PEI ethanol solution with a molecular weight of 18,000 to the solution obtained in step S1, and stir at 25° C. for 2 hours to obtain a solution containing the aminated carbon quantum dots.
[0105] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 5 nm.
[0106] S4, dispersing 0.005 g of nano zirconium oxide with a particle size of 20 nm and 0.005 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0107] Example 6
[0108] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0109] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in dichloromethane, add 0.25 mol of triphenylphosphine-NBS and 0.25 mol of pyridine and stir evenly.
[0110] S2. Add 0.2 mol of PEI dichloromethane solution with a molecular weight of 18,000 to the solution obtained in step S1, stir at -30°C for 4 hours, and warm to room temperature to obtain a solution containing the aminated carbon quantum dots.
[0111] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 5 nm.
[0112] S4, dispersing 1.5 g of nano zirconium oxide with a particle size of 50 nm and 0.5 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0113] Example 7
[0114] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0115] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in N,N-dimethylformamide, add 0.4 mol of dicyclohexylcarbodiimide solution and 0.4 mol of 4-dimethylaminopyridine solution and stir evenly.
[0116] S2, adding 0.2 mol of PEI N,N-dimethylformamide solution with a molecular weight of 18000 to the solution obtained in step S1, stirring at 25° C. for 24 hours to obtain a solution containing the aminated carbon quantum dots;
[0117] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 8 nm.
[0118] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 600 nm and 0.0375 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0119] Example 8
[0120] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0121] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in N,N-dimethylformamide, add 0.3 mol of diisopropylcarbodiimide and 0.3 mol of 1-hydroxybenzotriazole solution and stir evenly.
[0122] S2. Add 0.2 mol of PEI N,N-dimethylformamide solution with a molecular weight of 18,000 to the solution obtained in step S1, and stir at 25° C. for 10 hours to obtain a solution containing the aminated carbon quantum dots.
[0123] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 8 nm.
[0124] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 600 nm and 0.03 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0125] Example 9
[0126] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0127] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in acetonitrile, add 0.25 mol of benzotriazol-1-yloxy-tris(dimethylamino)phosphonium hexafluorophosphate and 0.25 mol of triethylamine, and stir evenly.
[0128] S2. Add 0.3 mol of PEI acetonitrile solution with a molecular weight of 18,000 to the solution obtained in step S1, and stir at 25° C. for 2 h to obtain a solution containing the aminated carbon quantum dots.
[0129] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 8 nm.
[0130] S4, dispersing 0.03 g of nano zirconium oxide with a particle size of 600 nm and 0.05 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0131] Example 10
[0132] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0133] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in N,N-dimethylformamide, add 0.25 mol of benzotriazol-1-yloxy-tris(tetrahydropyrrolyl)phosphonium hexafluorophosphate and 0.25 mol of 1-hydroxybenzotriazole solution and stir evenly.
[0134] S2. Add 0.2 mol of PEI N,N-dimethylformamide solution with a molecular weight of 18,000 to the solution obtained in step S1, and stir at 25° C. for 2 hours to obtain a solution containing the aminated carbon quantum dots.
[0135] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 8 nm.
[0136] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 600 nm and 0.025 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0137] Embodiment 11
[0138] This embodiment prepares a broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, comprising the following steps:
[0139] S1. Disperse 0.2 mol of carboxyl carbon quantum dots in N,N-dimethylformamide, add 0.25 mol of O-(N-succinimidyl)-bis(dimethylamino)carbonium tetrafluoroborate and 0.25 mol of 1-hydroxybenzotriazole solution and stir evenly.
[0140] S2. Add 0.2 mol of PEI N,N-dimethylformamide solution with a molecular weight of 1500 to the solution obtained in step S1, and stir at 40° C. for 4 hours to obtain a solution containing the aminated carbon quantum dots.
[0141] S3. The solution obtained in step S2 is centrifuged at a speed of 35000 rpm, the centrifugal product is collected, washed with water until neutral, and dried at room temperature to obtain aminated carbon quantum dots with an average particle size of 5 nm.
[0142] S4, dispersing 0.05 g of nano zirconium oxide with a particle size of 600 nm and 0.05 g of the aminated carbon quantum dots obtained in step S3 into 1 L of deionized water to obtain a widely distributed zirconium oxide-aminated carbon quantum dot nanofluid.
[0143] Comparative Example 1
[0144] This comparative example provides a narrow distribution aminated carbon quantum dot nanofluid, comprising the following steps:
[0145] 0.1 g of the aminated carbon quantum dots obtained in step S3 of Example 1 was dispersed in 1 L of deionized water to obtain an aminated carbon quantum dot nanofluid with a narrow distribution.
[0146] Test Example 1
[0147] The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid obtained in Examples 1-11 and the narrow distribution aminated carbon quantum dot nanofluid obtained in Comparative Example 1 were subjected to oil recovery tests respectively.
[0148] The oil recovery test process is as follows:
[0149] The low permeability outcrop sandstone core (core length: 5.0cm; core diameter: 2.5cm, gas permeability 10.3mD) was dried and weighed at room temperature, vacuumed and saturated with simulated formation water for 8h, left to stand for 24h and weighed again, and the porosity and pore volume were calculated; saturated with oil at a constant temperature of 55℃, the saturated crude oil volume was calculated, and aged for 48h; the core model was flooded with nanofluids at a flow rate of 0.2mL / min until the water content was 98%, the produced oil volume was recorded, and the water drive recovery factor (produced oil volume divided by saturated crude oil volume) was calculated. The recovery factor data are shown in Table 1.
[0150] Table 1 Nanofluid recovery data
[0151]
[0152]
[0153] As can be seen from Table 1, the wide distribution zirconium oxide-aminated carbon quantum dots prepared in the embodiment have obvious effects in improving the oil recovery rate of low permeability reservoirs. Compared with the pure water drive, the maximum recovery rate is nearly doubled. Compared with the narrow distribution aminated carbon quantum dot nanofluid drive in Comparative Example 1, the addition of large-particle-size nano-zirconia can effectively increase the swept volume of nanofluids in pore throats of different sizes, so that the recovery rate is significantly improved. In addition, the system is unstable when only nano-zirconia is used to configure nanofluids, and additional surfactants need to be added.
[0154] Within the limited ratio of zirconia nanoparticles and aminated quantum dots, the addition amount of zirconia nanoparticles is fixed, and the recovery rate decreases with the decrease in the mass fraction of aminated quantum dots, indicating that the aminated quantum dots have a strong ability to expel oil attached to ultrafine pore throats, and reducing the mass fraction of aminated quantum dots will reduce the overall oil recovery. Continuing to reduce the mass fraction of aminated quantum dots beyond the limited ratio, the system loses stability due to the decrease in the concentration of cationic surfactants, and the oil recovery rate drops significantly. Similarly, when the addition amount of aminated quantum dots is fixed and the mass fraction of zirconia nanoparticles is reduced beyond the limited ratio, the recovery rate will also drop significantly due to the decrease in the ability of nanofluids to expel oil attached to large-sized pore throats.
[0155] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid, wherein: The nanofluid comprises nano zirconium oxide, aminated carbon quantum dots and water; The aminated carbon quantum dots include carbon quantum dots and polyethyleneimine connected to the carbon quantum dots via amide bonds.
2. The broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid according to claim 1, wherein: The solid content of the nanofluid is 0.001% to 0.2%; wherein the mass ratio of the nano zirconium oxide to the aminated carbon quantum dots is (3 to 5):
3.
3. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 1, wherein: The aminated carbon quantum dots are obtained by an amidation reaction between carboxyl carbon quantum dots and polyethyleneimine.
4. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 1, wherein: The particle size of the nano zirconium oxide ranges from 20nm to 900nm.
5. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 1, wherein: The particle size of the aminated carbon quantum dots ranges from 2 nm to 10 nm.
6. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 1, wherein: The particle size of the nano zirconium oxide is in the range of 50nm to 300nm; The particle size of the aminated carbon quantum dots ranges from 5 nm to 10 nm.
7. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 1, wherein: The solid content of the nanofluid is 0.01% to 0.2%.
8. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 3, wherein: The specific preparation process of the aminated carbon quantum dots includes: Dispersing carboxyl carbon quantum dots in a reaction medium, adding a condensing agent and an activator solution and stirring evenly; then adding a polyethyleneimine solution to react to obtain a solution containing the aminated carbon quantum dots; The obtained solution is centrifuged, washed with water until neutral, and dried to obtain the aminated carbon quantum dots.
9. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The reaction medium is selected from at least one of deionized water, N,N-dimethylformamide, dimethyl sulfoxide, dichloromethane, tetrahydrofuran, tert-butyl methyl ether, cyclopentyl methyl ether, dimethyl carbonate, ethyl acetate, isopropanol, 2-methyltetrahydrofuran, 2-(N-morpholine)ethanesulfonic acid, acetonitrile, methanol, and ethanol.
10. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The reaction medium is deionized water.
11. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The condensing agent is selected from the group consisting of carbodiimide condensing agents, organic phosphorus condensing agents, onium salt condensing agents, 3-acyl-2-thiothiazoline, tris(2,6-dimethoxyphenyl)bismuth, N,N'-carbonyldiimidazole, and 4-(4,6-dimethoxytriazine-2-yl)-4-methylmorpholine hydrochloride.
12. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The condensing agent is dimethylaminopropylethylcarbodiimide hydrochloride.
13. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The active agent is selected from one of N-hydroxysuccinimide, 4-dimethylaminopyridine, 4-pyrrolidinylpyridine, 1-hydroxybenzotriazole, 1-hydroxy-7-azobenzotriazole, N-hydroxysuccinimide, N-hydroxyphthalimide, pentafluorophenol, triethylamine, diazabicyclic, and pyridine.
14. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The active agent is N-hydroxysuccinimide.
15. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The polyethyleneimine is selected from at least one of linear polyethyleneimine and branched polyethyleneimine, and the molecular weight of the polyethyleneimine is 1500-20000.
16. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The molar ratio of the carboxyl carbon quantum dots, the condensation agent, the activator and the polyethyleneimine is 1:(1-2):(1-2):
1.
17. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The molar ratio of the carboxyl carbon quantum dots, the condensation agent, the activator and the polyethyleneimine is 1:1.5:1.5:
1.
18. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The reaction temperature is -30°C to 40°C.
19. The broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to claim 8, wherein: The reaction time is 2h to 24h.
20. A method for preparing the broad distribution zirconium oxide-aminated carbon quantum dot nanofluid according to any one of claims 1 to 19, wherein: The preparation method comprises: dispersing nano zirconium oxide and aminated carbon quantum dots in water to obtain the wide-distribution zirconium oxide-aminated carbon quantum dot nano fluid.
21. Use of the broadly distributed zirconium oxide-aminated carbon quantum dot nanofluid according to any one of claims 1 to 19 in water flooding of low permeability / ultra-low permeability oil reservoirs.
Citation Information
Patent Citations
Method for preparing intelligent nanometer oil-displacing agent
CN104531118A
Nanofluid for deep profile control and preparation method thereof
CN110964491A
Method for synthesizing surface functional group modified carbon quantum dots and application to nano oil displacement
CN111234818A
Method for preparing nano zirconium dioxide carbon quantum dot composite material by one-pot method
CN112210365A
Carbon quantum dot modified polystyrene oil displacement material and preparation method thereof
CN112409606A
